Nikah Siri dan Dampaknya Terhadap Hak Perempuan dan Anak dalam Itsbat Nikah - Fitria Wahyu Ningrum (STIKes Ibnu Sina Ajibarang, 2025)
Nikah siri is a marriage conducted without official state registration, resulting in significant legal implications for women and children. Religiously, this type of marriage is considered valid; however, from the perspective of state law, the lack of official registration causes women to lose their rights as wives, such as financial support, inheritance rights, and legal protection within the household. Additionally, women in nikah siri marriages do not have a strong legal basis to file for divorce or claim their rights in court. Meanwhile, children born from nikah siri marriages only have a civil relationship with their mother, making it difficult for them to obtain a birth certificate that includes their father's name, inheritances, and rights to care and education from their father. This study aims to analyze the impact of nikah siri on women's and children's rights from a legal perspective and examine the role of itsbat nikah as a legal instrument in providing certainty and protection for affected women and children. This research employs a literature study method with content analysis of various legal texts and related regulations. The findings indicate that the absence of official registration for nikah siri leads to legal uncertainty, resulting in the loss of various rights for women and children. Itsbat nikah serves as a crucial solution to provide legal recognition and protection for those affected. Therefore, official marriage registration is essential to prevent various legal issues that could harm women and children within Indonesia’s legal system.